Upper crustal structure beneath the Ongul Island, East Antarctica - Ito, Kiyoshi; Ikami, Akira; Shibuya, Kazuo; Kaminuma, Katsutada (1984)
P(論文) Two explosion seismic experiments were conducted in 1980 by the 21st Japanese Antarctic Research Expedition (JARE-21) to reveal the velocity structure beneath the Ongul Islands, East Antarctica. In one experiment eleven stations were established along a line of 5.2 km long at intervals of about 0.5 km on the outcrops on East and West Ongul Islands and two explosions of 100 and 80 kg were fired at the bottom of the sea. The other smaller-scale experiment was made on East Ongul Island to reveal the structure shallower than that obtained by the above-mentioned experiment. Five shots were fired and the seismic waves were observed at eight stations along two lines of 0.7 and 0.9 km long respectively. In both experiments direct waves were clearly recorded at all the stations as first arrivals. The mean apparent velocity and the mean average velocity of P-waves are 6.19±0.11 and 5.74±0.88 km/s, respectively. The obtained velocity in the ice-free area of the Ongul Islands is nearly the same as the velocities under the ice sheet in East Antarctica hitherto obtained by the research expeditions of the United States, USSR and Japan. The sedimentary layer with a velocity less than 5.5 km/s does not exist. Clear later arrivals with large amplitude were also detected at all the stations that ranged from 0.1 to 5.2 km from the shot point. The mean apparent velocity and the mean average velocity were 2.84±0.03 and 2.94±0.37 km/s, respectively. These later arrivals are presumably Rayleigh waves. departmental bulletin paper